Event-triggered synchronization control for complex networks with actuator saturation - Liu, Dan; Yang, Guang-Hong (Neurocomputing (Amsterdam), 2018)
This paper investigates the problem of event-triggered synchronization control for complex networks. Each node is subject to actuator saturation. Based on Lyapunov theory and algebraic graph theory, novel sufficient conditions are derived, under which the synchronization error system is asymptotically stable. Compared with the existing results, the proposed event-riggered synchronization control strategy can be applied to the network with the unknown coupling configuration matrix. A numerical example is presented to demonstrate the effectiveness of the proposed control strategy.